2014
DOI: 10.1371/journal.pone.0106233
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Frequency Magnitude Distribution and the Visibility Graph in the Synthetic Seismicity Generated by a Simple Stick-Slip System with Asperities

Abstract: By using the method of the visibility graph (VG) the synthetic seismicity generated by a simple stick–slip system with asperities is analysed. The stick–slip system mimics the interaction between tectonic plates, whose asperities are given by sandpapers of different granularity degrees. The VG properties of the seismic sequences have been put in relationship with the typical seismological parameter, the b-value of the Gutenberg-Richter law. Between the b-value of the synthetic seismicity and the slope of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Here, we apply a recently developed method by Donges et al (2013a) to test for time series irreversibility that is based on horizontal visibility graphs (HVGs, Luque et al 2009;Lacasa et al 2012;Telesca et al 2014). HVGs are constructed from a time series (x(t i )) N i=1 such that each data point x i = x(t i ) of the time series is assigned to a node i of the graph.…”
Section: Has Been Applied Inmentioning
confidence: 99%
“…Here, we apply a recently developed method by Donges et al (2013a) to test for time series irreversibility that is based on horizontal visibility graphs (HVGs, Luque et al 2009;Lacasa et al 2012;Telesca et al 2014). HVGs are constructed from a time series (x(t i )) N i=1 such that each data point x i = x(t i ) of the time series is assigned to a node i of the graph.…”
Section: Has Been Applied Inmentioning
confidence: 99%
“…In recent decades, the theory of networks [97][98][99][100][101] has triggered many applications in seismicity (see, e.g., [47,60,[102][103][104][105][106][107][108]), which showed that the EQ network properties may reveal a seismic hazard [109][110][111][112][113][114]. Tenenbaum et al [60] introduced the EQ networks based on similar activity patterns (ENBOSAP) which are very useful for the NTA of seismicity [83].…”
Section: Introductionmentioning
confidence: 99%
“…Several further studies have been performed on the relationship between the b -value and the k–M slope, such as those focused on the shallow and deep Pannonian seismicities [ 17 ], in three dominant seismic areas of Northern Iran (Azerbaijan, Alborz, and Kopeh Dagh) [ 18 ], in 24 seismogenic zones in Alaska and Aleutian subduction zone at three depth ranges [ 19 ], in Taiwan and Italy [ 20 ]. Even laboratory seismicity, such as that generated by a mechanical stick-slip system with different roughness degrees [ 21 ], and physics-based synthetic seismicity [ 22 ] have shown that the b -value is closely linked to the k–M slope, suggesting that this relationship could be characterized by a type of universality.…”
Section: Introductionmentioning
confidence: 99%